ANALISIS EXTERNAL FACTOR EVALUATION (EFE) MATRIX DAN INTERNAL FACTOR EVALUATION (IFE) MATRIX PADA MASTERPIECE FAMILY KARAOKE KOTA BENGKULU - Meiffa Herfianti; Sulisti Afriani; Berian Saputra (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
Masterpiece family karaoke Bengkulu city, is one of the industry focusing in family entertainment by presenting adequate facilities and services and more practical karaoke system, also sell a variety of food and beverages and various promotional packages, the use of play songs play store applications Masterpiece KTV through mobile phones. This study aim is to determine the analysis of external and internal matrix in Masterpiece family karaoke Bengkulu city. Data collection methods in this study is to use questionnaires by giving questions to the 75 respondents. The analytical method used is an external internal matrix. From the calculation of external internal strategy factor, it is obtained that internal strategy factor score of 3.89 and total external factor strategy score of 3.87. From the results of this study masterpiece family karaoke city Bengkulu lies in cell 1 by using growth strategy that is growth and concentration through vertical integration. Growth strategy with vertical integration is a strategy done by expanding the company by taking over the function of the supplier or taking over the distributor's function.Keywords: Marketing Strategy, External Internal Matrix Analysis